The Experiential Museum – Avant-Garde Spatial Experiments and the Reorganization of the Human Sensorium - Meri Batakoja; Karin Šerman (Architektúra & urbanizmus, Department of Architecture of the Institute of History of the Slovak Academy of Sciences, 2021)
Avant-garde artistic experiments are unquestionably recognized as relevant to the museum field in the context of art and museum studies. This paper aims to reconfirm their relevance in the architectural context as well, selecting crucial cases and protagonists whose final products were not artworks or exhibitions per se, but new (concepts of) space. These new concepts of space were all treated as democratic and participatory new media capable of training and modernizing the whole of our human sensorium. In this way, a curious partnership is discovered between this “experiential” art museum and the discourse on architectural modernity. Imaginary space, expressionist space, correlational space, multimedia space and situationist space – these are the principal categories that this paper recognizes as five distinct productive devices for modernist perceptual reorganization.
Zážitkové múzeum – avantgardné priestorové experimenty a reorganizácia ľudského zmyslového vnímania
Keywords: art museum, modernity, avant-garde, experiential, experimental, modern architecture, space, architectural theory